MENGURAI PENGARUH SOCIAL MEDIA DAN FINANCIAL LITERACY TERHADAP INVESTMENT DECISION INVESTOR MUDA MELALUI HERDING EFFECT - Nur Faridatus Sholikhah; Nurjanti Takarini (STKIP Persada Khatulistiwa Sintang, 2026)
This study aims to analyze the impact of herding behaviour in mediating the relationship between social media exposure and financial literacy on the investment decisions of young investors affiliated with the UPN Veteran East Java Investment Gallery. This study involved 173 young investors selected using probability sampling. The research approach was quantitative, using an online questionnaire and analysis based on Partial Least Squares Structural Equation Modelling (SEM-PLS). The results of this study indicate a significant positive influence of social media exposure and financial literacy on investment decisions. Other findings indicate that herding behaviour is able to mediate complementarily in the influence of social media exposure on investment decisions and mediate competitively in the influence of financial literacy on investment decisions. This study is expected to enrich knowledge regarding the mediating role of herding behaviour within the framework of the Theory of Planned Behaviour and Social Learning Behaviour, which can emphasise the importance of financial literacy and digital literacy among young investors. The limitation of this study lies in the use of a limited sample at UPN Veteran East Jawa Investment Gallery, so it is recommended that future studies expand the scope of the research area.